INDIKASI FINANSIAL INCLUSION DI PERDESAAN DAN KONTRIBUSI BANK PEMBIAYAAN RAKYAT SYARIAH DALAM PENGEMBANGAN SEKTOR-SEKTOR PRODUKTIF - Harfandi, Harfandi; Putri, Hesi Eka (Alhurriyah, 2015)
The contribution of Islamic Rural Banking (popular as BPRS in Indonesia) in supporting of real sectors as financial inclusion’s indication, can be done by many program such as: 1) Increasing branch office and channeling office of Rural Banking, 2) Increasing the accessibility of rural banking for micro enterprises, 3) Implementing the service system which customer oriented and social justiced, 4) Expansion of the product which suitable for community, 5) Reinforcement the strategy in realizing financial inclusion 6) Reinforcement in regulation’s strategy, 7) Reinforcement in socialization’s strategy, 8) Reinforcement in competition’s strategy and 9) Reinforcement in human resource’s strategy.